2011
DOI: 10.1136/archdischild-2011-300532
|View full text |Cite
|
Sign up to set email alerts
|

Oral versus intravenous ibuprofen for patent ductus arteriosus closure: a randomised controlled trial in extremely low birthweight infants

Abstract: Oral ibuprofen is as effective as intravenous ibuprofen for PDA closure even in ELBW infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 29 publications
(50 reference statements)
4
63
0
2
Order By: Relevance
“…Oral, but not IV, ibuprofen was associated with rise in cystatin-C levels, a marker of impaired renal function, in preterm infants indicating that infants with borderline renal function may need careful monitoring [144]. Erdeve et al [145] performed an RCT of oral versus IV ibuprofen in 80 preterm infants and found a higher initial closure rate and reduction in the incidence of BPD with oral ibuprofen though there was a higher reopening rate in infants who received this treatment. A meta-analysis that included two studies ( n = 166) comparing oral ibuprofen with IV ibuprofen showed higher PDA closure rate with oral ibuprofen in comparison with IV ibuprofen and did not show a significant difference in adverse effects [146].…”
Section: How To Treat?mentioning
confidence: 99%
“…Oral, but not IV, ibuprofen was associated with rise in cystatin-C levels, a marker of impaired renal function, in preterm infants indicating that infants with borderline renal function may need careful monitoring [144]. Erdeve et al [145] performed an RCT of oral versus IV ibuprofen in 80 preterm infants and found a higher initial closure rate and reduction in the incidence of BPD with oral ibuprofen though there was a higher reopening rate in infants who received this treatment. A meta-analysis that included two studies ( n = 166) comparing oral ibuprofen with IV ibuprofen showed higher PDA closure rate with oral ibuprofen in comparison with IV ibuprofen and did not show a significant difference in adverse effects [146].…”
Section: How To Treat?mentioning
confidence: 99%
“…In contrast to high closure rates, several adverse effects have been reported with such medications, including gastrointestinal bleeding and perforation, weakened platelet aggregation, hyperbilirubinaemia and renal failure 1 2. The role of paracetamol as an alternative treatment for the closure of hsPDA has gained importance in recent years due to these potential side effects 3…”
mentioning
confidence: 99%
“…The most commonly used drugs for this purpose are cyclooxygenase inhibitors, mainly indomethacin and ibuprofen, which block the conversion of arachidonic acid to prostaglandins [1,2]. The reported treatment success with ibuprofen for the management of hsPDA is between 70 and 85% [3,4,5,6]. On the other hand, several adverse effects have been reported with such medications, including peripheral vasoconstriction, gastrointestinal bleeding and perforation, weakened platelet aggregation, hyperbilirubinemia and renal failure [7,8].…”
Section: Introductionmentioning
confidence: 99%